Per l’edizione dell’Asino d’oro boiardesco. Escussione completa dei testimoni - Matteo Favaretto (Annali Online dell'Università di Ferrara. Sezione Lettere, 2022)
The present article aims to provide the full collation between the surviving witnesses of Matteo Maria Boiardo’s Asino d’oro, on which the recent critical edition is based. A detailed description of the witnesses containing this vernacular translation of Apuleius’ Golden Ass is given at the outset: these include two manuscripts dated between the end of the 15th and the beginning of the 16th century as well as the editio princeps published in Venice in 1518. The examination of the conjunctive and separative errors shows that the witnesses all derive from a common archetype and that the stemma codicum is bipartite with the early printed book representing one independent branch and the two manuscripts – copies of the same antigraph – the other.